A clinical audit of red blood cell transfusion at National District Hospital - Madito, Nonofo Snowy (University of the Free State, 2021)
𝗕𝗮𝗰𝗸𝗴𝗿𝗼𝘂𝗻𝗱: Red blood cell transfusion is one of the most critical and expensive live-saving treatment modalities. Literature has shown that restrictive transfusion is safe and yields good patient outcomes. Evidence shows that a clinical audit is one of the most valuable instruments to determine if transfusion practices align with the guidelines and identify knowledge deficiencies. The National District Hospital was audited against the South African guidelines, including trigger conditions, administrative standards and monitoring requirements. 𝗔𝗶𝗺: To evaluate the red blood transfusion practice and patients’ outcomes at National District Hospital and determine adherence to transfusion guidelines. 𝗠𝗲𝘁𝗵𝗼𝗱𝘀: A retrospective descriptive study was conducted. Blood transfusion registers in the hospital were used to compile all transfusion episodes from 01 June 2019 to 31 December 2019. Files were retrieved from the admissions office using that list. A datasheet was used. The department of Biostatistics at the University of the Free State processed the data. 𝗥𝗲𝘀𝘂𝗹𝘁𝘀: One hundred eighteen (118) transfusion episodes occurred in the study period, 78 files could be retrieved, but only 76 met the inclusion criteria. The median age was 47. HIV (44.7%) was the most common comorbid condition. A large percentage of patients (81.6%) received oral iron as an additional treatment. Pre-transfusion haemoglobin was documented for all patients with a median of 4.6 g/dL. All ordered units were transfused. The audit revealed that 68% of the cases adhered to the guidelines. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻: Most of the transfusion episodes adhered to the guidelines. Training on transfusion medicine recommended.
Dissertation (M.Med.(Family Medicine))--University of the Free State, 2021
Keywords: Red blood cell; Blood transfusion practice; The National District Hospital; Training on transfusion medicine